ACTUAL PROBLEMS OF ORGANIZATION OF REGIONAL MEDICAL SERVICE FOR CHILDREN WITH JUVENILE ARTHRITIS - V.A. Malievskiy; G.R. Gareeva; R.Z. Akhmetshin ("Paediatrician" Publishers LLC, 2010)
Authors discuss organization of medical service for children with juvenile arthritis. Characteristics of PC program «Register of children with rheumatic diseases» is presented. The article describes problems of patients' provision with drugs and suggests measures of improvement of medical service for children with juvenile arthritis. Key words: children, juvenile arthritis, medical service, register. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):16-20)